The effects of hydrocortisone on rat heart muscarinic and adrenergic alpha 1, beta 1 and beta 2 receptors, propranolol-resistant binding sites and on some subsequent steps in intracellular signalling - Myslivecek, Jaromír; Rícný, Jan; Kolár, Frantisek; Tucek, Stanislav (Naunyn-Schmiedeberg's archives of pharmacology, 2003)
Glucocorticoids affect the expression and density of neurotransmitter receptors in many tissues but data concerning the heart are contradictory and incomplete. We injected rats with hydrocortisone for 1-12 days and measured the densities of cardiac muscarinic receptors, alpha(1)-, beta(1)- and beta(2)-adrenoceptors and propranolol-resistant binding sites (formerly assumed to be the putative beta(4)-adrenoceptor). Some aspects of intracellular signalling were also evaluated: we measured adenylyl cyclase activity (basal, isoprenaline- and forskolin-stimulated and carbachol-inhibited), the coupling between muscarinic receptors and G proteins and basal and isoprenaline-stimulated heart rate. The density of cardiac muscarinic receptors increased (in both the atria and the ventricles). The density of beta(1)-adrenoceptors increased in the atria and was little changed in the ventricles. The density of beta(2)-adrenoceptors increased in both the atria and the ventricles. The number of alpha(1)-adrenoceptors decreased initially, followed by a transient increase in the atria and did not change in the ventricles. The density of propranolol-resistant binding sites first increased and then diminished in the atria and did not change in the ventricles. Although there were noticeable changes in receptor densities, the stimulatory and inhibitory effects on adenylyl cyclase, basal and isoprenaline-stimulated heart rate and the coupling between muscarinic receptors and G proteins were not significantly altered. This may indicate that changes in receptor densities might be one of the mechanisms maintaining stable functional output.
Keywords: Receptors, Adrenergic, beta; Adrenergic beta-Antagonists; radioligandová zkouška; srdeční komory; beta-adrenergní receptory; Male; Receptors, Adrenergic; Rats, Wistar; receptory muskarinové; vazebná místa; Receptors, Adrenergic, alpha-1; beta-1-adrenergní receptory; Radioligand Assay; signální transdukce; Myocardium; Propanolamines; beta blokátory; mužské pohlaví; potkani Wistar; hydrokortison; Signal Transduction; Hydrocortisone; beta-2-adrenergní receptory; Glucocorticoids; Propranolol; krysa rodu Rattus; Binding Sites; Receptors, Adrenergic, beta-2; Animals; Receptors, Adrenergic, beta-1; glukokortikoidy; propanolaminy; zvířata; Rats; propranolol; Heart Ventricles; Receptors, Muscarinic; adrenergní receptory; alfa-1-adrenergní receptory; Injections, Subcutaneous; myokard; injekce subkutánní